Conversion of Cyclohexane to 6-Hydroxyhexanoic Acid Using Recombinant Pseudomonas taiwanensis in a Stirred-Tank Bioreactor - Bretschneider, Lisa; Heuschkel, Ingeborg; Wegner, Martin; Lindmeyer, Martin; Bühler, Katja; Karande, Rohan; Bühler, Bruno (Frontiers in Catalysis, 2021)
6-Hydroxyhexanoic acid (6HA) represents a polymer building block for the biodegradable polymer polycaprolactone. Alternatively to energy- and emission-intensive multistep chemical synthesis, it can be synthesized directly from cyclohexane in one step by recombinant Pseudomonas taiwanensis harboring a 4-step enzymatic cascade without the accumulation of any intermediate. In the present work, we performed a physiological characterization of this strain in different growth media and evaluated resulting whole-cell activities. RB and M9* media led to reduced gluconate accumulation from glucose compared to M9 medium and allowed specific activities up to 37.5 ± 0.4 U gCDW-1 for 6HA synthesis. However, 50% of the specific activity was lost within 1 h in metabolically active resting cells, specifying growing cells or induced resting cells as favored options for long-term biotransformation. Further, the whole-cell biocatalyst was evaluated in a stirred tank bioreactor setup with a continuous cyclohexane supply via the gas phase. At cyclohexane feed rates of 0.221 and 1.084 mmol min-1 L-1, whole-cell biotransformation occurred at first-order and zero-order rates, respectively. A final 6HA concentration of 25 mM (3.3 g L-1) and a specific product yield of 0.4 g gCDW-1 were achieved with the higher feed rate. Substrate limitation, product inhibition, and toxification by cyclohexane were identified as critical factors limiting biocatalytic performance. Future research efforts on these factors and precise adjustment of the cyclohexane feed combined with an in-situ product removal strategy are discussed as promising strategies to enhance biocatalyst durability and product titer and thus to enable the development of a sustainable multistep whole-cell process.